The Impact of Migration on Rural Poverty and Inequality : A Case Study in China - Zhu, Nong; Luo, Xubei (2012)
Large numbers of agricultural labor moved from the countryside to cities after the economic reforms in China. Migration and remittances play an important role in transforming the structure of rural household income. This article examines the impact of rural-to-urban migration on rural poverty and inequality in a mountainous area of Hubei province using the data of a 2002 household survey. Since migration income is a potential substitute for farm income, we present counterfactual scenarios of what rural income, poverty, and inequality would have been in the absence of migration. Our results show that, by providing alternatives to households with lower marginal labor productivity in agriculture, migration leads to an increase in rural income. In contrast to many studies that suggest that the increasing share of nonfarm income in total income widens inequality, this article offers support for the hypothesis that migration tends to have egalitarian effects on rural income for three reasons: (1) migration is rational self-selection--farmers with higher expected return in agricultural activities and/or in local nonfarm activities choose to remain in the countryside while those with higher expected return in urban nonfarm sectors migrate; (2) households facing binding constraints of land supply are more likely to migrate; (3) poorer households benefit disproportionately from migration.